What is The Level Technical Efficiency of Dairy Cooperative Association of Indonesia In East Java Province During Covid-19? - Atik Purmiyati; Thea Safira (East Java Economic Journal, 2024)
This research was conducted with the aim of analyzing the level of technical efficiency Dairy Cooperative Association of Indonesia (GKSI) in East Java Province. This research was conducted using a non-parametric approach, namely by using Data Envelopment Analysis (DEA). The input variables used in this research are the number of farmers, total population of dairy cows, and operational costs. The output variable used is total milk production. The results of this research show that the average technical efficiency level of GKSI member breeder cooperatives in East Java Province in 2019 was 74.8% and there were 9 efficient cooperatives, while in 2020 the average technical efficiency level of GKSI member breeder cooperatives in East Java Province was 85.6% and there are 11 efficient cooperatives.Cooperatives, Data Envelopment Analysis, Dairy Cooperative Association of Indonesia, Technical Efficiency